Bridge To Terabithia - Paterson, Katherine; Diamond, Donna (New York Harper Trophy, 1977)
The life of a ten-year-old boy in rural virginia expands when he becomes friends with a newcomer who subsequenly meets an untimely trying to reach their hideaway, Terabithia, during a storm
American Corner
Winner Of The JOHN Newbery Medal
11
Keywords: Death -- Fiction; English Fiction; English Stories; Friendship -- Fiction